(3Pjd eQBg GdReGf aj JGQjN GdCYjGf dSHW GHf GdLhRis - (3GdbWH ehSi Hf eMeO Hf CMeO Gdjhfjfj GdHYdHcjs; (3SHW GHf GdLhRj , jhSa Hf bRGhZdj Hf YHO Gddg GdHZOGOj GdOeTbj GdMfaj, TeS GdOjf CHh GdeXaQ ,SHW GHf GdLhRj,J (B654 (3g` s ((3eMeO Hf eMeO GdfSJQGhj s)
(3ChdgG (B:s
(3Chd eGajg ef CKfGA JQLeI fLe GdOjf GdoHZOGOi ef hajGJ SfI (B655 (3g` s
(3BNQgG (B:s
(3hjfJgj Edi BNQ SfI (B686 (3g` s
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs